Impact of UHMWPE and PP Polymer Characterization on the Blending Process for PP/UHMWPE Composite in FFF - Nur Aiman, Fakrul; Kamarudin, K.; Rahim Jamian; Sun, Shufeng; Shaari, M. F.; Roslan, Mohd. Nazrul; Ahmad, A; Mohd Khairuddin, M. S.; Raman, I. (International Journal of Integrated Engineering, 2024)
Ultra-high molecular weight polyethylene (UHMWPE) is a thermoplastic semicrystalline polymer renowned for its exceptional wear resistance, low friction coefficient, and robust mechanical properties. It also exhibits strong resistance to corrosive substances. Despite these unique characteristics, UHMWPE has an extremely low melt flow rate (MFR) near zero, making it unsuitable for traditional polymer processing techniques. To address this issue, polypropylene (PP) is often used as a plasticizer to enhance the extrudability of UHMWPE-based composites. PP, a widely used thermoplastic polymer, is synthesized from the monomer propylene via chain-growth polymerization. However, chemical incompatibility between UHMWPE and PP poses challenges in composite manufacturing. This research aims to examine the characteristics of both materials to better understand the requirements and impact of these properties on the blending process of UHMWPE-PP composites for Fused Filament Fabrication (FFF). The characterization process includes analyzing the morphological, thermal behaviour and stability, and crystallinity of UHMWPE and PP in their respective powder and granular forms. The study reveals how the particle shape influences the behaviour of both polymers and the outcomes of their blending. Comprehensive characterization informs the blending process, ensuring a homogeneous mixture and improved interfacial adhesion. The discoveries presented in this paper are implemented in examining the extrudability of UHMWPE-PP composites, incorporating various blending materials, for the specific application of bone repair implants using FFF.